1998
DOI: 10.1128/iai.66.11.5147-5156.1998
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the tpr Protease Gene of Porphyromonas gingivalis Is Regulated by Peptide Nutrients

Abstract: The Tpr protease of Porphyromonas gingivalis W83 is a membrane-associated enzyme capable of hydrolyzing chromogenic substrates for trypsin and bacterial collagenases. A previous study by us indicated that Tpr expression was increased under conditions of nutrient limitation. In the present study, we further characterized expression of the tpr gene using atpr::lacZ reporter gene construct under a range of nutrient conditions. In P. gingivalis, transcription of tpr was initiated 215 bp upstream of the coding regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…This effect of iron limitation, however, was probably due to a decrease in the culture growth rate since a similar change in gene expression was observed in a P. gingivalis 381 culture grown either slowly on diluted medium (351) or in chemostatcontrolled conditions (219). A second very well-designed study which concentrated on the regulation of tpr gene expression has yielded significant seminal information (208). It was found that Tpr proteinase production is negatively controlled by the increased availability of peptides, especially those containing phenylalanine, but not by free amino acids.…”
Section: Regulation Of P Gingivalis Proteinase Expressionmentioning
confidence: 88%
See 2 more Smart Citations
“…This effect of iron limitation, however, was probably due to a decrease in the culture growth rate since a similar change in gene expression was observed in a P. gingivalis 381 culture grown either slowly on diluted medium (351) or in chemostatcontrolled conditions (219). A second very well-designed study which concentrated on the regulation of tpr gene expression has yielded significant seminal information (208). It was found that Tpr proteinase production is negatively controlled by the increased availability of peptides, especially those containing phenylalanine, but not by free amino acids.…”
Section: Regulation Of P Gingivalis Proteinase Expressionmentioning
confidence: 88%
“…Peptides and cleaved collagen fibers generated at this step would then become substrates for periodontain and the Tpr proteinase. Significantly, as described above, the Tpr proteinase would initially be strongly upregulated by a deficiency of peptide nutrients (208) providing P. gingivalis with more proteolytic power in periods of starvation. Peptides and partially degraded proteins produced at this stage would also become perfect targets for periodontain, which cleaves very efficiently only peptides and denatured proteins, and without any discrete specificity for selected amino acid residues.…”
Section: The Role Of P Gingivalis Peptidases In Acquisition Of Nutrimentioning
confidence: 92%
See 1 more Smart Citation
“…These factors may have a bearing on the observed poor expression of P. gingivalis genes in E. coli from endogenous promoters. The mRNAs of two genes which are expressed in E. coli, tpr and ¢mA, have each been shown to be initiated from a site other than that used in P. gingivalis [10,12].…”
Section: Genementioning
confidence: 99%
“…Recently, the complete genome of P. gingivalis strain W83 has been determined (www.tigr.org) and although amino acid sequences can be deduced using this approach, little information can be gathered regarding the regulatory elements of these genes, and how protein expression is controlled. Transcription start points (tsp) have been reported for the P. gingivalis genes, prtT, which encodes a cysteine proteinase [7], hemR, a haemin-regulated gene [8], the groESL operon [9], the proteinase tpr [10], sodA the superoxide dismutase gene [11] and the ¢mbrillin gene ¢mA [12]. Promoter-like sequences were subsequently designated for prtT, groESL and tpr using the Escherichia coli sigma-70 (c 70 ) consensus binding sequence, although E. coli is only distantly related to the Porphyromonas genus [13].…”
Section: Introductionmentioning
confidence: 99%